Dynamic Modelling of Nickel Complexation in Xylem Sap of Quercus ilex: A Voltammetric Study - dos Santos, Margarida Maria Correia; Alves, Sheila; de Lurdes SimõesGonçalves, Maria; Nabais, Cristina (Electroanalysis, 2006)
Holm oak (Quercus ilex) is the dominant tree growing on serpentine soils of northeast Portugal, characterized by elevated soil concentrations of Ni and Mg, combined with low Ca concentrations. Apparently Q. ilex does not suffer from excessive concentrations of Ni in the soil. In this work we report a complexation study of nickel by the relevant ligands present in xylem sap: histidine, aspartic acid, oxalic and citric acids, at 0.10 M ionic strength and pH 5.5. Single and mixed complexes were characterized. To validate the proposed complexation model, diluted solutions of Q. ilex xylem sap were titrated with nickel. All studies were done using square-wave voltammetry (SWV) at a hanging mercury drop electrode. Due to the dynamic nature of SWV, it is possible to obtain the conditional stability constants of the complexes formed but also to have knowledge on the kinetics of the interconversion of the species present.
The following values have no corresponding Zotero field: publisher: WILEY-VCH Verlag
Keywords: Inert complexes; Mixed complexes; Nickel; Quercus ilex; Semidynamic complexes; Voltammetry; Xylem sap

Dynamic Modelling of Nickel Complexation in Xylem Sap of Quercus ilex: A Voltammetric Study - dos Santos, Margarida Maria Correia; Alves, Sheila; de Lurdes SimõesGonçalves, Maria; Nabais, Cristina (Electroanalysis, 2006)
Holm oak (Quercus ilex) is the dominant tree growing on serpentine soils of northeast Portugal, characterized by elevated soil concentrations of Ni and Mg, combined with low Ca concentrations. Apparently Q. ilex does not suffer from excessive concentrations of Ni in the soil. In this work we report a complexation study of nickel by the relevant ligands present in xylem sap: histidine, aspartic acid, oxalic and citric acids, at 0.10 M ionic strength and pH 5.5. Single and mixed complexes were characterized. To validate the proposed complexation model, diluted solutions of Q. ilex xylem sap were titrated with nickel. All studies were done using square-wave voltammetry (SWV) at a hanging mercury drop electrode. Due to the dynamic nature of SWV, it is possible to obtain the conditional stability constants of the complexes formed but also to have knowledge on the kinetics of the interconversion of the species present.
Keywords: Inert complexes; Mixed complexes; Nickel; Quercus ilex; Semidynamic complexes; Voltammetry; Xylem sap